Pomegranate Byproduct Extracts as Ingredients for Producing Experimental Cheese with Enhanced Microbiological, Functional, and Physical Characteristics - Lucia Parafati (MDPI AG, 2021)
Pomegranate peel and mesocarp, considered as wastes of fruit processing, are rich sources of beneficial phytochemicals, including hydrolyzable tannins and flavonoids, with proven antimicrobial and antioxidant activity, which can be employed for improving the overall quality of food products. In the present study, extracts from pomegranate peel (PPW) and mesocarp (PMW) were obtained through a water extraction method and evaluated for in vitro antimicrobial activity and polyphenol content. The two extracts were then added during the cheese-making process in order to create a new functional cheese with improved microbiological and physico-chemical characteristics. Antimicrobial in vitro assays evidenced a substantial efficacy of both extracts against Staphylococcus aureus, which often causes staphylococcal food poisoning outbreaks linked to the consumption of raw milk cheeses and artisanal cheeses. For this reason, a simulated cheese contamination was carried out in order to assess if pomegranate extracts can exert antimicrobial activity towards this pathogen even when incorporated into the cheese matrix. Milk enriched with pomegranate extracts (PPW and PMW) was used to produce two different experimental cheeses, which were then evaluated for yield, polyphenol content, and microbiological as well as physico-chemical traits throughout the refrigerated storage. Despite the low concentration of the extracts, the treated cheeses showed an increase in firmness and a slight decrease in S. aureus counts, of more than one log unit in comparison to the control cheese, for up to 12 d of cold storage. Such results support the reuse of agro-food byproducts, in substitution to chemical food preservatives, as the key to a circular economy.